KEDUDUKAN KOMISI PEMBERANTASAN KORUPSI SEBAGAI LEMBAGA EKSEKUTIF DITINJAU BERDASARKAN TEORI PHILIP BOBBIT - Nabila Alif Radika Shandy; Abhinaya Wahyu Satrio (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2023)
The Publication of Constituion Number 19 year 2019 about the second change of Constitution number 30 year 2002 about Komisi Pemberantasan Tindak Pidana Korupsi in Indonesia to deal with corruption cases become a polemic in public. This happened because of the institutional status of KPK from independent to executive. This research propose one problem formulation, how to analyze the judicial review of changes on KPK Constitution as an executive institution using Phillip Bobbit’s interpretation method? The research method used in this research is normative, using primary and secondary legal material and using descriptive qualitative analysis. This research gives a result that review of KPK as an executive institution with Philip Bobbit’s interpretation method emphasized on judicial review of changes on KPK Constitution in historical, textual, doctrinal, structural, ethical, and prudential.